Power Frequency Breakdown Properties of LDPE-Doped Inorganic Nanoparticles - Yujia Cheng; Guang Yu (Molecules)
Although polyethylene is widely used in electrical insulation, it does not possess dielectric properties. It is therefore desirable to develop insulation materials with excellent dielectric properties. In this study, low-density polyethylene (LDPE) was used as a matrix resin, while MgO, wollastonite, and montmorillonite (MMT) were employed as inorganic nano-additives. Three composites were prepared using the boiling–melt blending approach. Power frequency breakdown tests were performed on the original LDPE and on the prepared nanoparticle/LDPE composites. Upon combination with the Weibull distribution, the breakdown test results revealed that the addition of these nano-additive particles to the LDPE matrix increased the breakdown field strength of the material. The highest breakdown field strength for the nano-MgO/LDPE composite was obtained using a MgO loading of 0.5%. Notably, the obtained value was 1.8% higher than that of the pure LDPE. In addition, the highest breakdown field strength for the nano-wollastonite/LDPE composite was obtained using a wollastonite loading of 1% (7.48% higher than that of pure LDPE). Similarly, the highest breakdown field strength of the nano-MMT/LDPE composite was obtained using an MMT loading of 3%, giving a value that was 6.67% higher than that of the pure LDPE.